PENGARUH KONSENTRASI CAMPURAN PEREKAT KANJI DAN SAGU TERHADAP MUTU BRIKET LIMBAH KULIT KOLANG KALING (Arenga pinnata Merr.) - Imam Mahadi; Zulfarina Zulfarina; Yoana Ulitua Panggabean (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
The rapid growth of Indonesia's population has resulted in increasing national energy needs which require alternative energy. Alternative energy that can be made is briquettes by producing biomass waste. The purpose of this study was to obtain the quality of charcoal briquettes from kolang forth skin waste using a mixture of starch and sago flour as an adhesive. In this study there were tests for water content, ash content, heat and density. The completely randomized design (CRD) method was used in this study, with 5 treatments and 3 replications. Obtained research results using kolang forth shell waste can be used to make charcoal briquettes. Average water content and ash content comply with SNI 1-6235-2000. The best water content value was found in treatment E (0% starch adhesive : 30% sago adhesive) which was 3.8%. The best ash content value was found in treatment A (30% starch adhesive: 0% sago adhesive) which was 5.87%. The calorific value did not meet SNI but met Japanese standards and the best treatment results were found in treatment C (15% starch adhesive: 15% sago flour) which was 5,470 cal/gr. Meanwhile, the density values ​​do not meet SNI but meet British standards for all treatments. The best density value was found in treatment A (starch adhesive 30: sago adhesive 0) which was 0.84%.